UMP QS 5-Star University to pursue good values, governance and integrity - Pejabat, Naib Canselor UMP (Pejabat Naib Canselor, 2018)
1. UMP QS 5-Star University to pursue good values, governance and integrity 2. Agreements Exchanged between UMP and Mercedes-Benz (M) Sdn. Bhd. 3. ‘Gerobok Rezeki #BPACare’ Project launched